Prevalence of acute reactions to gluten contamination of the diet in children with celiac disease - Pjetraj, Dorina; Damiani, Denise; Monachesi, Chiara; Ricci, Salima; Ascani, Milena; Gatti, Simona; Catassi, Carlo; Lionetti, Elena (Frontiers in Pediatrics, 2025)
Background and aimThe prevalence and clinical spectrum of symptoms due to inadvertent gluten exposure in children with celiac disease (CeD) on a gluten-free diet (GFD) are not well defined. This study aimed to assess these acute reactions through an online survey.MethodsParents of children with CeD treated with a GFD for at least 12 months completed an online questionnaire. The survey focused on symptoms occurring within 24 h of gluten-contaminated food ingestion.ResultsData were collected for 296 children. Acute reactions after unintentional gluten ingestion were reported in 98 cases (33.1%). The most common symptoms were abdominal pain (57.1%), diarrhea (42.9%), vomiting (31.6%), headache (12.2%), and fatigue (14.3%). Less frequent symptoms included nausea, constipation, urticaria, aphthous stomatitis, and arthropathy (each ∼5%–7%). In 86% of cases, symptoms appeared within 2–3 h. Gluten exposure most often occurred while dining out, especially in restaurants and school cafeterias.ConclusionsOne-third of children with CeD on a GFD experience acute reactions to accidental gluten ingestion. These reactions typically arise rapidly and are dominated by gastrointestinal symptoms, aligning with reports from existing literature, where vomiting and nausea have been observed in 3%–46% of patients at the time of CeD diagnosis and in 13%–61% during gluten challenge.